Electroacupuncture Ameliorates Cerebral Ischemic Injury by Inhibiting Ferroptosis - Li, Guangda; Li, Xiaoxiao; Dong, Jianjian; Han, Yongsheng (Frontiers in Neurology, 2021)
ABSTRACT Backgroud:Evidences suggest that ferroptosis is involved in the pathologic process of ischemic stroke. We aimed to investigate the inhibiting effects of electroacupuncture(EA) on ferroptosis and the mechanism of EA in the treatment of ischemic stroke. Methods: In this study, MCAO rats were established according Zea method and treated by EA for 7 days. We analyzed the coordinated motor deficit, and the volume of cerebral infarction in vivo using 9.4T MRI. Then, the ischemic brain tissue was taken out. The levels of malondialdehyde (MDA), superoxide dismutase(SOD), glutathione(GSH) and iron were investigated according manufacuture’s kit. Western blot and RT-qPCR were used evaluating the expression of GPX4, transferrin(Tf), transferrin receptor1(TfR1) and ferritin heavy chain1(FTH1). To further confirm the results, we used transmission electron microscope (TEM) to observe the morphology of mitochondria. Results：EA intervention significantly improved coordinated motor deficits and decreased cerebral infarct volume in MCAO rats. EA can downregulate the level of MDA, iron and upregulat the level of SOD , GSH. Besides, EA increased the expression of GPX4 and FTH1, decreased the expression of Tf and TfR1. Additionly, EA promote the recovery of mitochondrial morphology in ischemic cerebral tissue. Conclusion：Our results show that EA can inhibit ferroptosis by regulating oxidative stress and iron homeostasis relative protein. Keywords：Electroacupuncture ; Ischemic stroke; Ferroptosis; mitochondrial; iron homeostasis